Underpricing and aftermarket performance of American depositary receipts (ADR) IPOs - Diro Ejara, Demissew; Ghosh, Chinmoy (Journal of Banking & Finance, 2004)
American depositary receipts (ADRs) are negotiable instruments representing foreign company shares traded in US dollars in the US capital market. We present comparative analyses of the pricing and aftermarket performance of Initial Public Offerings (IPOs) by ADRs and a matching sample of US firms over the 1990–2001 period. Offered by large, well-known multinationals, ADR IPOs go through a detailed scrutiny, and incur significant costs, during the pre-IPO period to recast financial statements in conformity with SEC rules and the US GAAP. This mitigates the information asymmetry between the IPO firm and investors. We categorize the ADR issuing country as developed or emerging, and our sample includes several cases of privatization of state owned corporations. The analyses indicate that (1) ADR IPOs are significantly less underpriced than comparable US IPOs; (2) IPOs from developed countries are more underpriced; and (3) Privatization IPOs are less underpriced than non-privatizations. The lower underpricing of ADR IPOs persists even after differential IPO attributes, the traditional proxies for information asymmetry and, the unique characteristics associated with ADR IPOs, are accounted for. We conclude that extant literature offers only partial explanation for this puzzling phenomenon.